2014
DOI: 10.1038/mt.2013.216
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Efficacy of SYL040012, a Novel siRNA Compound for Treatment of Glaucoma

Abstract: Glaucoma is a progressive ocular syndrome characterized by degeneration of the optic nerve and irreversible visual field loss. Elevated intraocular pressure (IOP) is the main risk factor for glaucoma. Increased IOP is the result of an imbalance between synthesis and outflow of aqueous humor (AH). Blocking β2 adrenergic receptor (ADRB2) has shown to reduce IOP by decreasing production of AH at the ciliary body (CB). SYL040012 is a siRNA designed to specifically silence ADRB2 currently under development for glau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 43 publications
0
65
0
1
Order By: Relevance
“…Additionally, the delivery of siRNAs in vivo into tumors was 10-and 30-fold more effective than that using cationic liposomes and naked siRNAs, respectively (Landen et al, 2005;Halder et al, 2006). Moreover, locally delivered siRNA has also been successfully used in the eyes, respiratory system, and pancreatic cancer (Zamora et al, 2011;Zorde Khvalevsky et al, 2013;Martínez et al, 2014), suggesting further potential for MRP4 siRNA.…”
Section: The Potential Of Mrp4 As a Drug Targetmentioning
confidence: 98%
“…Additionally, the delivery of siRNAs in vivo into tumors was 10-and 30-fold more effective than that using cationic liposomes and naked siRNAs, respectively (Landen et al, 2005;Halder et al, 2006). Moreover, locally delivered siRNA has also been successfully used in the eyes, respiratory system, and pancreatic cancer (Zamora et al, 2011;Zorde Khvalevsky et al, 2013;Martínez et al, 2014), suggesting further potential for MRP4 siRNA.…”
Section: The Potential Of Mrp4 As a Drug Targetmentioning
confidence: 98%
“…SYL040012 (bamosiran, by Sylentis, S.A.), targeting β2-adrenergic receptor, was shown to decrease intraocular pressure in normotensive and hypertensive animal models [88]. In a phase I trial initiated in 2009, SYL040012 eye drops was reported to be safe and well-tolerated.…”
Section: Clinical Experience With Sirna-based Therapeuticsmentioning
confidence: 99%
“…siRNA is also pursued for glaucoma therapy. siRNA targeting β 2 -adrenoceptors (SYL040012) was shown to reduce the expression of β2 adrenergic receptor and the production of aqueous humor, thereby reducing intraocular pressure [19]. …”
Section: Therapeutic Applications Of Sirna and Target Genesmentioning
confidence: 99%